Transcription factor-based classification of pituitary adenomas / PitNETs: a comparative analysis and clinical implications across WHO 2004, 2017 and 2022 in 921 cases - Isabella Nasi-Kordhishti; Mirko Hladik; Kosmas Kandilaris; Felix Behling; Jürgen Honegger; Jens Schittenhelm (Acta Neuropathologica Communications)
Abstract The WHO classifications of 2017 and 2022 recommend the use of pituitary transcription factors PIT-1, T-PIT and SF-1 as well as GATA3 and ERα for histopathological diagnosis. The aim of this study is to demonstrate their diagnostic impact in a large retrospective cohort. 921 PitNETs/PAs diagnosed in our department between October 2004 and April 2018 were retrospectively reassessed according to the WHO classifications 2017 and 2022. The original classification (WHO 2004) and the clinical data were retrieved from the patient records. Hormone-immunonegative null cell adenomas represented the largest subgroup (397 of 921) in the WHO 2004 classification. Of these, 377 were reclassified as gonadotroph PitNETs/PAs, and 14 were assigned to a non-gonadotroph hormone-producing cell line. Only 6 cases remained null cell tumors. 27 of 35 plurihormonal adenomas were assigned to a specific cell line in the 2017 and 2022 WHO classifications. Of 489 adenomas formerly classified as expressing of 1 or 2 hormones, the histopathological diagnosis was confirmed in 459 cases with the use of TP. Of the remaining 30 cases, 12 cases with positive immunostaining of 2 hormones could be assigned to a single cell line, and 18 cases changed their lineage. The correct correlation with clinical data significantly improved from 75.4% (WHO 2004) to 96.2% (WHO 2017 and 2022). Corticotroph PitNETs showed the highest risk for recurrence (21.9%) and progression (55.8%). The new classification enables more accurate (sub)classification and significantly improves clinicopathological correlation. In individual cases, it is essential to consider the reclassification to predict the clinical prognosis and to schedule the follow-up accordingly.